Fibromyalgia: dental aspects - Maria Panchovska; N Nikolov; E Firkova; Zl Kolarov (Научно-практическая ревматология)
Fibromyalgia is a disease accompanied by diffuse chronic pain for >3 months and tenderness on palpation in at least 11 of 18 anatomic points (American College of Rheumatology criteria). Gnathalgia was also included in the revised fibromyalgia criteria in 2010. Some patients have facial pain spots, symptoms and signs of temporomandibular dysfunction in combination with chronic fatigue and sleep disorder. The paper presents the results of an anonymous questionnaire survey in patients with a valid diagnosis of fibromyalgia. The patients with this disease require a follow-up by a family physician, a rheumatologist, and a dentist.